Material thinking: The theory and practice of creative research - Carter, Paul (Melbourne Melbourne University Press, 2004)
This intimate account of how ideas get turned into artwork?including dance performance, film, sound installation, sculpture, and painting?looks at how the material thinking that art embodies produces new understandings about individuals, their histories, and the cultures they inhabit. Discussing the philosophy of signs (images, text, and their interaction), the psychology of visual perception, and the overarching notion of mythopoeic place-making, this intellectually wide-ranging and anecdotally narrated primer provides a fresh perspective to the concept of inventing. All active practitioners in the fields of performance, media, film, museum, painting, sculpture, and cultural studies will benefit from this look at how artists participate in the conceptual invention of their world.